Identification of three new phase II metabolites of a designer drug methylone formed in rats by N-demethylation followed by conjugation with dicarboxylic acids - Židková, Monika; Linhart, Igor; Balíková, Marie; Himl, Michal; Dvořáčková, Veronika; Lhotková, Eva; Páleníček, Tomáš (Xenobiotica; the fate of foreign compounds in biological systems, 2018)
1. Methylone (3,4-methylenedioxy-N-methylcathinone, MDMC), which appeared on the illicit drug market in 2004, is a frequently abused synthetic cathinone derivative. Known metabolic pathways of MDMC include N-demethylation to normethylone (3,4-methylenedioxycathinone, MDC), aliphatic chain hydroxylation and oxidative demethylenation followed by monomethylation and conjugation with glucuronic acid and/or sulphate. 2. Three new phase II metabolites, amidic conjugates of MDC with succinic, glutaric and adipic acid, were identified in the urine of rats dosed subcutaneously with MDMC.HCl (20 mg/kg body weight) by LC-ESI-HRMS using synthetic reference standards to support identification. 3. The main portion of administered MDMC was excreted unchanged. Normethylone, was a major urinary metabolite, of which a minor part was conjugated with dicarboxylic acids. 4. Previously identified ring-opened metabolites 4-hydroxy-3-methoxymethcathinone (4-OH-3-MeO-MC), 3-hydroxy-4-methoxymeth-cathinone (3-OH-4-MeO-MC) and 3,4-dihydroxymethcathinone (3,4-di-OH-MC) mostly in conjugated form with glucuronic and/or sulphuric acids were also detected. 5. Also, ring-opened metabolites derived from MDC, namely, 4-hydroxy-3-methoxycathinone (4-OH-3-MeO-C), 3-hydroxy-4-methoxycathinone (3-OH-4-MeO-C) and 3,4-dihydroxycathinone (3,4-di-OH-C) were identified for the first time in vivo.
Keywords: Male; LC-HRMS; Rats, Wistar; methylone; Biotransformation in rats; Methylation; metylace; mužské pohlaví; potkani Wistar; nové syntetické drogy; krysa rodu Rattus; methamfetamin; Animals; Methamphetamine; Dicarboxylic Acids; kyseliny dikarboxylové; Designer Drugs; zvířata; conjugation with dicarboxylic acids; Rats; designer drug